The Effectiveness of Biopesticide Use on Chili Plants (Capsicum annuum) in Matoa Village, Prafi District, Manokwari Regency, Papua - Nurlailah; Sutiharni; Ayuningtias, Nandini; Andriyani, Liz Yanti (Open Global Scientific Journal, 2025)
Background: Organic farming has become crucial amid various environmental issues, the decline of beneficial insects, and reliance on synthetic chemicals. The use of biopesticides is one environmentally friendly solution.Aims: This study aims to determine the effectiveness of biopesticides in controlling major pests in chili plants cultivated in Matoa Village, Prafi District, Manokwari Regency.Methods: This experiment used three treatments: control, conventional chemical pesticides, and biopesticides, repeated 5 times. Experiment was conducted from February to June 2024.Results: The results showed that biopesticides significantly reduced pest attacks, especially thrips and fruit borers, but there was no significant difference for aphids and whiteflies compared to chemical pesticide treatments. Although the initial knockdown effect of biopesticides is slower, their long-term stability in pest suppression proved beneficial. Yield analysis showed that biopesticide-treated fields produced higher fruit quality and marketable yields comparable to those from chemical treatments. Farmer perception surveys highlighted positive views regarding safety and sustainability.Conclusion: The findings suggest that biopesticides are a viable, environmentally friendly alternative for integrated pest management in tropical farming systems. Overall, this study provides empirical evidence on the potential role of biopesticides in supporting sustainable agriculture and food security in eastern Indonesia, offering both local relevance and broader applicability to similar agroecological contexts.